POLA DISTRIBUSI Acacia decurrens Willd. DI JALUR PENDAKIAN CANDI CETHO GUNUNG LAWU - , LENY WIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Distribution pattern is essential characteristic of plantation that could affect the growth and its dynamics during stand development. Spatial distribution is the distribution of individuals with survival and reproduction over a field or space that can be influenced by climate. This distribution is often referred as population distribution. In the spatial distribution, there are three basic patterns: regular, random, and clumped. Research aimed to determine the distribution pattern of Acacia decurrens Willd. through Cetho Temple Mount Lawu Route Observation of Acacia decurrens was undertaken that was divided into 11 research stations. This species found at the height of 1,500 meters above sea level up to 2,500 meters above sea level up. Nested sampling plots each observation station were made on for 3 replications. The data were then processed to determin the distribution pattern by determining the value of Index of Disperse, the ratio between the value of the population variance with the average value of the population. The results showed that scattered Acacia decurrens clustered at the level of seedlings, saplings, poles and trees. Index of Disperse value is 2.24 for seedlings